2019
DOI: 10.1039/c8cp06955g
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of charges and polymer mechanical stiffness in the mechanism and kinetics of formation of liponanoparticles probed by the supported bilayer model approach

Abstract: Parameters controlling the mechanism and kinetics of formation of liponanoparticles are determined using supported lipid bilayer models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…LNPs contain three compartments, namely, the NP core, a thin water layer and the lipid bilayer. The thickness of the water layer has been measured by various authors, using lipid bilayers formed on planar and spherical supports, and different techniques such as neutron reflectivity or 1 H NMR. It was found in the 0.6–3 nm range. The thickness of a bilayer adsorbed to a PDLLA layer, as deduced from atomic force microscopy height pictures, was 3.9 ± 0.4 nm. , Therefore, we expected an increase in the particle size of about 12 nm corresponding to 2­[lipid bilayer thickness + water layer], compared to PDLLA NPs.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…LNPs contain three compartments, namely, the NP core, a thin water layer and the lipid bilayer. The thickness of the water layer has been measured by various authors, using lipid bilayers formed on planar and spherical supports, and different techniques such as neutron reflectivity or 1 H NMR. It was found in the 0.6–3 nm range. The thickness of a bilayer adsorbed to a PDLLA layer, as deduced from atomic force microscopy height pictures, was 3.9 ± 0.4 nm. , Therefore, we expected an increase in the particle size of about 12 nm corresponding to 2­[lipid bilayer thickness + water layer], compared to PDLLA NPs.…”
Section: Resultsmentioning
confidence: 96%
“…The highest content of lipid observed for LNP 90/10 is coherent with cryo-TEM images which showed that at 10% DOTAP, the NP surface was covered with intact vesicles. Increase in cationic lipid content resulted in a stronger electrostatic interaction between vesicles and particles, followed by vesicle breaking and fusion to form a lipid bilayer. , The ratio of DOTAP in the LNP shell increased with the initial amount of DOTAP added to the formulation: 17, 35, and 58 mol % instead of 10, 25.5, and 46.5 mol % in corresponding liposomes. This result agreed with expectations because DOTAP would preferentially adsorb to the negatively charged NP surface compared to POPC. ,, The equivalent number of lipid bilayers was estimated by assuming that a lipid bilayer fully covering the NPs had a total surface area ( A v ) equal to that of the NPs (i.e., A v / A p = 1) .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations